Superoxide dismutase activity in tear fluid and blood of patients and mouse model of amyotrophic lateral sclerosis: a pilot study - Pavlenko, Tatiana A.; Chesnokova, Natalia B.; Beznos, Olga V.; Shikareva, Natalia N.; Nodel, Marina R.; Shevtsova, Ksenia V.; Panina, Uliana V.; Shteinberg, Daniil A.; Kukharskaya, Olga A.; Sukhanova, Iuliia S.; Pukaeva, Nadezhda E.; Kukharsky, Michail S.; et al. (PeerJ, 2025)
Amyotrophic lateral sclerosis (ALS) is a severe neurodegenerative disease characterized by progressive degeneration of motor neurons and skeletal muscle atrophy. The heterogeneity of clinical symptoms and the lack of reliable biomarkers hamper diagnostics of ALS. The dysfunction of superoxide dismutase 1 (SOD1) protein is considered one of the molecular mechanisms underlying ALS pathology. We measured total SOD activity in the tear fluid and blood serum of ALS patients, healthy volunteers, and in the ALS mouse model, harboring the human truncated form of fused in sarcoma (FUS) protein—FUS (1–359). The average SOD activity in tear fluid did not differ between ALS patients and the control group. However, an increased proportion of patients with low SOD activity in tear fluid was observed compared to the control group. In contrast, SOD activity in blood serum was higher in the ALS group. Transgenic FUS (1–359) mice showed decreased SOD activity in tear fluid at both presymptomatic and symptomatic stages of ALS. SOD activity in blood serum did not differ between transgenic and control animals. These findings suggest that changes in SOD activity in the tear fluid of ALS patients and transgenic FUS (1–359) mice reflect local metabolic disturbances in the eyes associated with ALS.
Keywords: Superoxide dismutase; Amyotrophic lateral sclerosis; Transgenic animals; FUS-proteinopathy; Biomarkers